Technical Assistance to the Agriculture Development Task Force in Afghanistan - World Bank (Washington, DC, 2013)
This report summarizes the main outputs of the technical assistance provided which was concentrated in three areas: (1) development of MAIL's strategic priorities and investments for the immediate future/short term, medium term and longer term; (2) advising Ministry of Agriculture, Irrigation and Livestock (MAIL) regarding the design of an appropriate structure of the Ministry and definition of corresponding responsibilities; (3) analytical policy advice regarding urgent issues that the Ministry of Agriculture (MAIL) has to deal with on a daily basis, but where it lacks the capacity to analyze alternative policy strategies and solutions. The technical assistance work regarding urgent policy issues has focused on three main areas: (1) organization and management of public food grain stocks; (2) purchasing and distribution of improved wheat seed; and (3) leasing of government-owned land to private entities. Finally, and outside the area of policy support, the Bank may consider stepping up its efforts to help MAIL to further develop/restore Afghanistan's agricultural production base and in this way help improving the livelihoods of poor rural people. More specifically the Bank may consider exploring the Government's interest in a project aimed at increasing agricultural incomes through improvements in the quality and reliability of input delivery systems and wider adoption of improved production technologies, including technologies that increase the efficiency of on-farm water management.